Video review of the frequency and assessment of head impacts during the FIFA Arab Cup 2021 - Serner, A.; Araujo, J.; Beasley, I.; Boyce, S. H.; Byrne, M.; Geertsema, L.; Grimm, K.; Massey, A. (Science and Medicine in Football, 2023)
We used injury spotters and video footage review to establish the frequency of head impacts, their characteristics, and the subsequent medical assessment during the FIFA Arab Cup 2021TM. Six defined video signs of potential concussion based on an international consensus were used. A total of 88 head impacts were observed, with a median of 2 (IQR 1.5-4, range 0-7) head impacts per match, of which 44 (50%) resulted in on-pitch medical assessment. The median assessment duration was 51s (IQR 34-65s, range 19-262s). The most common mechanism was head-to-head contact (27% of all impacts and 43% of impacts with medical assessment). Seven head impacts showed video signs of potential concussion: six had one sign and one had two signs. The concussion substitution was used in three incidents. Head impacts during the FIFA Arab Cup were common and a median of 1 head impact per game required an on-pitch medical assessment. Only 8% of the head impacts showed any video sign of potential concussion, and only 3% resulted in a concussion substitution. The medical on-pitch assessments appeared too short (<1 min) to allow an appropriate assessment of all head impacts, indicating a need for further evaluation. Further standardisation of the injury spotter`s role in football is recommended.